Manajemen Risiko Laboratorium dalam Meningkatkan Keselamatan dan Kesehatan Kerja (K3): Sebuah Studi Literatur - Wilda Ummairah; Junaidin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Laboratory risk management is a systematic approach aimed at identifying, analyzing, evaluating, and controlling various potential hazards that arise in laboratory activities. The laboratory environment poses a high level of risk because it involves the use of hazardous chemicals, biological agents, sharp equipment, and electrical installations that have the potential to cause workplace accidents. This study aims to examine the concepts and implementation of laboratory risk management to improve occupational safety and health (OSH). The method used is a literature review analyzing various scientific sources, journals, and relevant laboratory safety guidelines from the past five years. The results of the study indicate that risks in laboratories can be minimized through the implementation of effective risk management, including risk identification, hazard level assessment, and control measures via standard operating procedures (SOPs), the use of personal protective equipment (PPE), and workplace safety training. In addition, a safety culture and organizational commitment are critical factors in the successful implementation of risk management. Thus, the implementation of optimal risk management can create a laboratory environment that is safe, efficient, and productive.